The Trend of Critical Thinking Studies in Biology Education through Online Learning: A Systematic Review - Nuri, Ayu Rahma Ulfa; Sajidan, Sajidan; Ramli, Murni (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2021)
Biology teachers and students in society 5.0 are expected to show critical thinking skills (CTS) in solving problems or making decisions. Thus, it is important to know how the CTS are nurtured through online learning. The trend of studies on these issues needs to be explored. This research aims to map the trend of studies on nurturing the CTS through online learning by reviewing some articles published within 2018-2020, considering 1) the online learning, 3) topics in biology, 4) teaching methods, and 5) instruments of CTS. Following the systematic review of the PRISMA Method, articles were screened from Google Scholar. The keywords were